PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PEMASARAN PADA CV. PUTRA JAYA PERKASA - Ansori, Putra Budi; Andriani, Ade (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
The purpose of this study was to determine the effect of workload on the performance of marketing employees at CV. Putra Jaya Perkasa. This research was conducted at CV. Putra Jaya Perkasa on Jl. Parit Indah No.70 G, Bukit Raya District, Pekanbaru. The population in this study were employees of the marketing department at CV. Putra Jaya Perkasa numbered 33 people. In determining the number of samples, researchers used a census that took part of the population represented by 32 marketing employees. The results of the research on the research model and the submission of hypotheses proposed in this study produced the following conclusions: Based on the statistical value of the workload t is 3.759 with a significance value of 0.001. These results indicate that workload affects the performance of marketing employees at CV. Putra Jaya Perkasa. The number of correlations (R) is 0.320 where these numbers indicate that the workload on the performance of marketing employees at CV. Putra Jaya Perkasa has 32% influence. So it can be concluded that the workload affects the performance of marketing department employees on the CV. Putra Jaya Perkasa